Perspectives of bereaved relatives of patients with haematological malignancies concerning preferred place of care and death: A qualitative study. (May 2019) - McCaughan, Dorothy; Roman, Eve; Smith, Alexandra G; Garry, Anne C; Johnson, Miriam J; Patmore, Russell D; Howard, Martin R; Howell, Debra A
Background: People with haematological malignancies have different end-of-life care patterns from those with other cancers and are more likely to die in hospital. Little is known about patient and relative preferences at this time and whether these are achieved. Aim: To explore the experiences and reflections of bereaved relatives of patients with leukaemia, lymphoma or myeloma, and examine (1) preferred place of care and death; (2) perceptions of factors influencing attainment of preferences; and (3) changes that could promote achievement of preferences. Design: Qualitative interview study incorporating 'Framework' analysis. Setting/participants: A total of 10 in-depth interviews with bereaved relatives. Results: Although most people expressed a preference for home death, not all attained this. The influencing factors include disease characteristics (potential for sudden deterioration and death), the occurrence and timing of discussions (treatment cessation, prognosis, place of care/death), family networks (willingness/ability of relatives to provide care, knowledge about services, confidence to advocate) and resource availability (clinical care, hospice beds/policies). Preferences were described as changing over time and some family members retrospectively came to consider hospital as the 'right' place for the patient to have died. Others shared strong preferences with patients for home death and acted to ensure this was achieved. No patients died in a hospice, and relatives identified barriers to death in this setting. Conclusion: Preferences were not always achieved due to a series of complex, interrelated factors, some amenable to change and others less so. Death in hospital may be preferred and appropriate, or considered the best option in hindsight.